“Just play” the piano player inside: An exploration of an informal learning practice on formal piano education in a Dublin music school - Robbins, June (Trinity College (Dublin, Ireland). School of Education, 2021)
This phenomenological study focuses on applying and assessing the impact of an informal learning approach, in a formal piano education setting in Dublin. The synthesis of two music worlds is investigated as polarities on a continuum (Folkestad, 2008). Interest in this area arose from experience of students’ disenchantment with their own musical interests not being met on one hand, alongside engaging with the typical classical path of the Royal Irish Academy of Music (RIAM) piano local centre piano grade examinations. Green (2014), Green and Baker (2014), Folkestad (2008) and Varvarigou (2014) extend knowledge surrounding the informal music education landscape. Specifically, Green’s (2014) Hear Listen Play (HeLP) is aimed at instrumental teachers who want to incorporate informal learning and non-formal teaching into formal musical environments. Chawke (2018) and Moore (2018) provide additional and specific evidence that the HeLP programme would work in Ireland. A natural progression of this growing body of research is to analyse the success of an informal practice on a piano environment in Dublin. On one hand, an Irish piano examination culture exists but there is limited recent research available. Transferrable research was needed from Poland, China, Australia and the UK to support this thesis’ central agenda. This thesis builds on deepening existing knowledge in the area of synthesising informal and formal practices in piano education. Despite its’ exploratory nature, this study offers some insight into how to proficiently assess the success of the HeLP project. After a thorough examination of informal and formal piano education, technical skills, musical abilities, assessment and limitations in the literature review, this study uses familiar and unfamiliar musical activities to assess the HeLP intervention in an Irish context. A mixed methods study occurred. Tools included visual data capture of musical activities, interviews and Gordon’s (1969b) musical aptitude profile (MAP) assessments. Due to Covid-19, these activities were captured by participants before and after the HeLP intervention to track any progress. These were collated on Microsoft Sway. Participants and critical friends examined the attempts to provide multiple voices to assess success. Based on averages, performances remained the same; sight-reading, aural and playing by ear slightly decreased alongside improvements in improvisation MAP tonal and rhythm scores. Pre- and post-interviews obtained the students’ voices and highlighted their rise in confidence. This mix of quantitative and qualitative data collection enabled potential bias to be minimised. Remarkably, this is the first study which focuses on specific and familiar assessments to locate it firmly within an Irish piano education research context. Keywords: informal learning; formal piano education; piano pedagogy; piano technique; synthesis; musical ability; technical skill; transferrable skills; non-formal teaching; HeLP intervention; ear play; improvisation; aural skills.
Keywords: Master in Music Education; Education